Religion, politics and society in modern Turkey: 1808-2023 - Gözaydın, İştar (Edinburgh studies on modern Turkey, 2024)
This book is a critical reading of Turkey’s entanglement and struggle with modernity, Islam, diversity, democracy and human rights/liberties slightly less than the last two centuries. Its major argument is that the relationship between religion and state forms an important dimension not only of official state ideology, but also in interrelations between different groups in society and in those groups’ relations with the state. The book provides an overarching view of modern Turkey’s religion, politics and society over an extended period and examines the complex relations between society, religion, laicité, state identity and their reflections in state power and daily life. This book’s originality and novelty and what makes this study different from others in the market is its provision of an overarching view of religion, politics, and society in modern Turkey over an extended period starting from Ottoman times era current times